Pelatihan Penerapan Note-Taking System Untuk Meningkatkan Pemahaman Konsep Bagi Guru SMPIT Madani Pekanbaru - Prih Febtiningsih; Siti Niah; Wandi Syahfutra; Pahmi Pahmi; Ardiya Ardiya; Agung Prasetyo Wibowo (LPPM UMRI, 2020)
The community service undertaken aims to provide training to the teachers of SMPIT Madani Pekanbaru in order to increase the ability of teachers to understand the concept of material provided by presenters from various sources from seminars, workshops, FGDs or other activities, make it easier for teachers to remember the material presented and be more focused and also help teachers in compiling and processing information obtained through interesting notes so that they are easier to recall what they got in the material delivered by the presenters. To achieve the objectives of this community service (PPM) activity, the implementers used the lecture, discussion and practicum methods so that the trainees could easily understand the material provided at the training. The activities carried out were participated by the teachers at SMPIT Madani Pekanbaru. This activity is on target as evidenced by the enthusiasm of the teacher in following the entire process of activities. They are very active in discussing and interacting when given a material concept and instructing them to take notes with various Note-taking Systems. Keywords: Community Service, Note-taking System, Understanding the Concept